IMPLEMENTASI SISTEM COMPARE DATA STOCK DI PT. GELAEL SIGNATURE - Joko Suwarno; Iwan Giri Waluyo; Hardiansyah; Sartika Lina Mulani Sitio (CV. Multi Kreasi Media, 2025)
This research aims to find out how much influence brand trust, brand awareness and perceived quality have on customer purchasing decisions at the Gelael MT Haryono Supermarket. Gelael Signature sells various types of retail goods, such as household utensils, not only selling retail goods, Gelael Signature also sells various daily necessities such as food, drinks, vegetables, and so on. The system development method for this application uses the SDLC method with a waterfall model which consists of 5 stages. These stages are needs analysis, system design, implementation, testing and maintenance. This application was built using the PHP programming language, MySQL database as the database. Based on the concept and design, this research produces a web-based goods inventory information system at PT. Gelael Signature.